2018
DOI: 10.1136/bjophthalmol-2018-312133
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and biofilm of corneal sutures

Abstract: Evidence for active bacterial and biofilm presence on corneal sutures was found. Corneal sutures should be considered for removal sooner, before becoming exposed and/or keratitis-related. Traditional culture studies and SEM imaging are helpful in investigating biofilm and its clinical importance. More studies of the spectrum of bacterial growth on embedded biomedical devices such as corneal sutures are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…In suture-related PKIK cases, infected corneal sutures should also be sent for microbiological culture as they may provide additional information. Adler et al ( 107 ) evaluated the presence of microbial growth and biofilm formation amongst corneal sutures removed following astigmatic correction (quiescent), loosening or breakage (exposed), or infection. Biofilms are composed of extracellular matrix secreted by microorganisms and are usually resistant to conventional antimicrobial treatment ( 108 , 109 ).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In suture-related PKIK cases, infected corneal sutures should also be sent for microbiological culture as they may provide additional information. Adler et al ( 107 ) evaluated the presence of microbial growth and biofilm formation amongst corneal sutures removed following astigmatic correction (quiescent), loosening or breakage (exposed), or infection. Biofilms are composed of extracellular matrix secreted by microorganisms and are usually resistant to conventional antimicrobial treatment ( 108 , 109 ).…”
Section: Diagnosismentioning
confidence: 99%
“…Biofilms are composed of extracellular matrix secreted by microorganisms and are usually resistant to conventional antimicrobial treatment ( 108 , 109 ). They have been shown to form on biotic and abiotic surfaces, including sutures ( 107 , 110 ). In their study, the infection group demonstrated a culture yield of 60% based on corneal sutures, underlining corneal suture material (when infected) as a useful source for obtaining microbiological diagnosis.…”
Section: Diagnosismentioning
confidence: 99%
“…The AM graft could be secured with sutures or fibrin glue. However, sutures may cause stitch reaction and elevate the risk of stitch abscess, granulation formation and infection [17]. Sutureless AM graft with fibrin glue has the potential to drop due to gravity or during blinking.…”
Section: Discussionmentioning
confidence: 99%
“…Current AMT techniques involve suturing the graft or patch of AM over the ocular surface. Nevertheless, the corneal sutures can not only cause postoperative pain and discomfort to patients [25] but also lead to complications such as additional trauma, suture abscesses [26,27], infections [28,29], granuloma formation [30], and tissue necrosis [31]. Furthermore, the inflammatory effect of corneal suture [32] can lead to an unsuccessful repairing attempt, especially if the corneal damage is due to an inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%